Acesso aos direitos estabelecidos pelo estatuto da pessoa idosa: Diferenciais por raça/cor - Ana Amélia Camarano de Mello Moreira; Daniele Fernandes; Carolina de Freitas Pereira; Thamires da Silva Ribeiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The objective of the text is to analyse whether access to rights guaranteed by the Bill of Elderly occurs differently between the black and non-black population and between men and women. The first right established is the right to life which is violated by various causes, some is possible to be avoided by actions of the State, Family or Society. For example, the deaths by external or non -natural causes play an important role in the total deaths of this population. They represent 3.7% of the deaths that could be avoided and are more frequent among men; 4.3% of the total. Among these causes, the most important are the falls, followed by transport accidents and events whose intention is undetermined and for aggression. The impact of these deaths on life expectancy at birth is 3.1 years lost and at 60 years, 0.5 years of life. With this, the probability of a male newborn reaches old age is reduced from 85% to 79% and at 60 years of reaching 80 could be 44%, but is reduced to 39%. These differentials are even greater if the race/color is considered. The intersection between sex and race leads to a difference of 12.4 years in the mean age at death for non black women when compared to black men. Black elderly people reported a worst health condition, which reflects in the growth of hospitalizations by falls and transport accidents. These are the ones that most use the public health system, which may be reflecting their unfavourable socioeconomic conditions and difficulty access to social services. It is important the development of public actions to promote and prevent the health of the elderly black population, with special attention to the black man. Considering the right to housing and friendly environment, there were great architectural and urbanistic challenges to be faced in Brazil, especially in the northern region. The construction and/or adequacy of private and urban infrastructure equipment as well as increasing accessibility, mobility and safety are important for promoting the right to aging with autonomy, integration and social participation for the growing elderly population. Synthesizing, access to the rights established by the Elderly Bill is not enjoyed by the same way by the elderly Brazilians. The heterogeneity of this population requires public policies that consider their differences. It is important to consider regional differences as well. A resident of the Northern Region ages in more adverse conditions than the resident in the Southeast. Increasing life expectancy is a great achievement to be celebrated, but it occurs differently between men and women, black and non -black etc .... Besides this, the quality of life of the long-lived is still a goal to be persecuted, in order to add "more life to the lived years" and it can be an important step towards building "a society for all ages" and that everyone can benefit from these gains.
Keywords: 18; J11; I14; I18; I30; K38; 330; Elderly Statute; race; rights; violence; health; mortality